Management of Nematodes with Cowpea Cover Crops - Koon-Hui Wang; Robert McSorley (EDIS)
Cover crops are crops grown between cash crop cycles, or crops intercropped with cash crops to cover the ground, such as in vegetable fields, orchards, groves, and agricultural sites. If used appropriately, cover crops can improve soil structure and fertility, decrease soil erosion, provide foliage and animal feed, and suppress crop pests such as weeds, insects, nematodes, and other plant pathogens. Residues from cover crops can be incorporated as green manure to supply nutrients and improve fertility for the next crop. Using cover crops can increase on-farm crop diversity, may enhance many beneficial organisms, and possibly even contribute to carbon sequestration. One good example of a cover crop is cowpea, Vigna unguiculata (L.) Walp. This document is ENY-712, one of a series of the Department of Entomology and Nematology, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Date first printed: August 2004.